A New Method-Discrete Numerical Method for Computing Radius of Curvature based on the Cam Profile Equation - Fan Wu; Chang Yong (Jixie chuandong)
The radius of curvature of the cam profile is an important parameter,which directly reflects the degree and shape characteristics of the cam profile. It plays an important role in the analysis and design of the cam mechanism. A simple and effective method is proposed to solve the value of radius of curvature by taking the idea of "discrete-limit". The advantage of the new method which is more simple and direct,doesn’t need the complicated analytical derivation. The correctness of the new method is checked and proved through an example. The above research results enrich and deepen an understanding and awareness of the disc cam mechanism,which has important reference values and guiding significance to expand the radius of curvature of the solution.